Analisis Diagnosis Penyakit Ikan Lele Berbasis Website Menggunakan Metode Forward Chaining Dan Certainty Factor - Sukirman Sukirman; Fahri El Fazza; Nursuci Putri Husain (Jurnal Ilmiah Informatika, 2023)
There are several new symptoms and new types of diseases in catfish farming. Through this website, catfish farmers can find out how to prevent and solve catfish diseases. The Expert System Development Life Cycle is the study methodology utilized an expert system with a forward chaining mechanism as a decision, while the certainty factor is a supporter of confidence for the diagnosis of catfish disease. Confidence from experts and users on the type of flatulence with a value of 74% while a little confidence in the type of intestinal rupture and the bacterium Flexibacter columnaris with a value of 30%.